Calcaneal Apophysitis (Sever’s Disease): MRI Findings - Dogan, Mehmet S; Doganay, Selim; Koc, Gonca; Gorkem, Sureyya B; Ciraci, Saliha; Coskun, Abdulhakim (Journal of Nepal Paediatric Society, 2016)
Calcaneal apophysitis (Sever’s disease), is the most frequent cause of the heel pain in growing children. The diagnosisis generally made with a typical history and clinical examination. Imaging modalities including radiography and magnetic resonance imaging can help establish the diagnosis. In this case we report imaging findings of an 11-year-old boy diagnosed as Sever’s disease. J Nepal Paediatr Soc 2015;35(2):172-174